Health-related quality of life and depression in Rett syndrome caregivers - Sarajlija Adrijan; Đurić Milena; Kisić-Tepavčević Darija (Vojnosanitetski Pregled)
Background/Aim. Rett syndrome (RTT) is a severe neurodevelopmental disorder primarily affecting females with an estimated incidence of 1 : 10,000-15,000 female births. Currently, there is no specific treatment that halts or reverses the progression of RTT. Therefore, management was mainly symptomatic, focussed on optimising patient's abilities. The aim of this study was to investigate factors influencing health-related quality of life (HRQoL) and depression in mothers who care for children with Rett syndrome (RTT) in Serbia. Methods. The cross-sectional study was conducted on 49 mothers giving care to females with RTT. Caregivers` HRQoL was assessed by using the SF-36 questionnaire. Clinical severity score (CSS) of RTT patients and Beck Depression Inventory II (BDI -II) scale were used to quantify RTT severity and mothers` depression, respectively. Statistical assessment included descriptive statistics, ttest, Pearson correlation coefficient and multiple logistic regression. Results. The age of mothers ranged from 22 to 55 years and of their affected children from 3 to 29 years. Severe depression was observed in 15 (30.6%) participants. CSS and BDI - II scores correlated negatively with all SF- 36 domains and composite scores. Lowest scoring domains of HRQoL in mothers giving care to RTT children were mental health, vitality and role functioning emotional. Multiple linear regression analysis revealed that severity of RTT patients` disability (CSS) and caregivers` age are factors with strongest influence to HRQoL and depression in care giving mothers. Conclusion. Mothers giving care to children with RTT are at high risk of severe depression and lower HRQoL scores of domains that reflect mental well-being. Results of this study can help in planning subsequent interventions directed at families dealing with Rett syndrome.